Thief of night - Black, Holly (Charlatan duology, 2025)
"Charlie Hall used to be a talented con artist and thief with a knack for survival--until her last job nearly killed her. Instead of walking away, she bartered her freedom to the Cabal, a ruthless circle of elite gloamists who'd trapped Charlie's boyfriend, a powerful shadow named Vince. As the Cabal's new Hierophant, Charlie hunts rogue shadows on their behalf--not out of loyalty, but because it keeps Vince out of their hands. Or, at least, what's left of him. The tether that the Cabal used to bind Vince to Charlie erased every memory he had of her, leaving behind only Red--a dangerous Blight with Vince's face, but without his heart. Cold, ruthless, and angry, Red doesn't trust Charlie; he doesn't even like her. So when she's pressed into service by the Cabal's most manipulative member, Mr. Punch, she's on her own. She's no investigator, just a thief in over her head, sent to track down the Blight behind a brutal church massacre. Worse, her own shadow is planning to betray her. Charlie's in danger, and her troubles keep growing like a quickened shadow--fed on blood, twisted, and hungry. With carnage all around her and an irresistible weakness for bad decisions, Charlie has one last chance to save herself, but the price might be the one person she thought she couldn't bear to lose..."--Inside jacket flap.